Pendayagunaan Zakat, Infaq dan Shodaqah dalam Pemberdayaan Anak Panti Asuhan melalui Pendidikan pada Yayasan Panti Asuhan di Surabaya - Riduwan Riduwan (Universitas Muhammadiyah Surabaya, 2022)
ABSTRACT The purpose of this study is to find out and analyze how the utilization of zakat, infaq and shadaqah in empowering orphanages through education and the role of orphanages in educational empowerment. The research methodology used is descriptive qualitative research, data collection used is observation, interviews, and documentation. Data analysis was carried out by data reduction, data presentation and drawing conclusions. The results of this study concluded that the concept of utilization that was applied to the orphanage foundation in Surabaya in the distribution of zakat, infaq and shadaqah funds for the empowerment of orphanage children through education was used fully for the benefit of foster children both for education costs and living expenses, in the orphanage education empowerment program. care prioritizes formal education. Keywords: Empowerment of ZIS, Empowerment of Orphanage Children, Education